Menggali Makna Ijma' Dan Qiyas Dalam Penetapan Hukum - Alfan Syafa, Miftah Dzul; Sucipto, Imam (An-Nisa: Journal of Islamic Family Law, 2024)
This research is motivated by the fact that the Al-Quran and Hadith are the main sources in determining the law. In addition to these two religious texts, there are also Ijma' and Qiyas as methods in determining the law, both of which are the basis and method that has been agreed upon by the scholars. This discussion is interesting because this research will reveal how the steps of the Ijma' and Qiyas methods in determining a law and answering problems. This research is qualitative research with a normative approach and descriptive analysis, sourced from literature (library research). The primary source used is the book Ushl al-Fiqh al-Islam by Wahbah al-Zuhaili, and then the secondary sources used consist of books, journals, and other scientific works that are still related to the discussion. The technique in collecting data uses literature study techniques and is then analyzed properly. The results of this study show that as a source of Islamic law, Ijma' according to language is a deal, agreement, concurrence, or unanimity. According to the term, Ijma' is the agreement of the mujtahids from the people of the Prophet Muhammad at his time about the case of shar'i after the death of the Prophet Muhammad SAW. Meanwhile, Qiyas linguistically means measure, compare, or equate something with another. According to the term Qiyas, it is uniting something that is not mentioned in the nash with something mentioned by the nash due to the similarity of the illat between the two.